Findings from a Rapid Assessment of Avoidable Blindness (RAAB) in the Southwest Region of Kyrgyzstan. (3rd March 2020) - Mueller, Brigitte; Ibraimova, Sabina; Mamutalieva, Elzat; Limburg, Hans; Ibraimova, Aigul; Paduca, Ala
ABSTRACT: Purpose : Reliable data on eye care needs in Kyrgyzstan are not readily available. The purpose of this study was to determine the prevalence and causes of blindness and visual impairment in persons aged 50 and above in the southwest of Kyrgyzstan and to support the Ministry of Health (MoH) in the planning of eye care in the region. Methods : A population-based survey was conducted in three states (Oblast) in the southwest region of Kyrgyzstan. Sixty clusters of 50 people aged 50 years and older were selected by probability proportionate to size sampling. Ethical approval was obtained from the MoH, consent was obtained from each participant. Results : A total number of 3, 000 persons aged 50 and older were sampled. Among these 2, 897 (95.9%) were examined. The prevalence of bilateral blindness was 1.7% [95%CI: 1.1–2.4]. Cataract (43.3%) was the main cause of blindness, followed by glaucoma (30%), age-related macular degeneration (ARMD) (8.3%), other posterior segment diseases (6.7%) and non-trachomatous corneal opacities (5%). The prevalence of blindness and visual impairment increased strongly with age. The cataract surgical coverage in blind persons was 59%. Conclusion : Cataract and glaucoma were the major causes of blindness and visual impairment in persons 50 and above. The majority of the causes (85%) were avoidable, with 45% (cataract and uncorrected aphakia) treatable, 6.7% (corneal opacity and phthisis) preventable by primary health care/eye care services and 33.3% (cataract surgical complications, glaucoma) preventable by specialized ophthalmic services. The data suggest that an expansion of eye care services to reduce avoidable blindness is needed, as ageing will lead to an increase in older people at risk and a higher demand for eye care in the future.